Examining the dominant models and theories of international staffing policies and practices through the lenses of the African context and Chinese multinational construction enterprises in Africa - (:unkn) unknown (My University, 2021)
International staffing policies and practices of Chinese enterprises in Africa have given rise to a number of observations, critical comments, empirical support and rebuttals. One of the areas of research and critique has been the implications of the staffing policies and practices for knowledge and skills transfer to their African hosts. The availability of local skills and talent as constraints to change employment practices by Chinese enterprises has also received attention of researchers. We argue that the dominant international staffing models and theories are inadequate for a comprehensive understanding and critiquing of staffing practices of Chinese MNEs in Africa. Therefore, this paper adopted Zoogah, D. B., Peng, M. W., and Woldu, H. (2015a. Institutions, Resources, and Organizational Effectiveness in Africa. Academy of Management Perspectives, 29(1), 7–31) dynamic African business environment context to interrogate the utility of the dominant international staffing models and theories in order to understand and explain Chinese staffing policies and practices in Africa. The paper also used Chinese Multinational Construction Enterprises (CCMNEs) as a lens through which to examine the relevance of the African context. The paper advances a series of questions to guide future research. We argue that if pursued, the questions can help further our understanding of why the staffing policies and practices of multinational companies from emerging economies in Africa might focus on recruiting PCNs and the casualization of African workers.
Keywords: African Research